Manejo contable del presupuesto del Gobierno Autónomo Descentralizado de La Parroquia Caracol Provincia Los Ríos- año 2019 - Jiménez Briones, Gustavo Adolfo (2020)
The following case study is presented focused on the accounting management of the budget carried out in the Autonomous Decentralized Parish Government of Caracol corresponding to the 2019 period, in which consultations of the accounting-budget process applied by the planning council and the assembly were carried out parish, emphasizing the processes of very small amounts. It was observed that they have deficiencies in the execution of the budget; Furthermore, it does not carry out the follow-up process in planning by the Commission who, together with the council and assembly, establish the budget. It is also emphasized that, according to the lack of monitoring of the budget planning, they are not able to meet the needs of the Caracol community in general.